Penggunaan Kinemaster dan Quizziz dalam Pembelajaran Fisika untuk Meningkatkan Hasil Belajar Siswa - Emor, Injilia Trifena; Mondolang, Aswin Hermanus; Lolowang, Jimmy (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
This study aims to improve student learning outcomes using the Kinemaster and Quizziz applications using classroom action research methodology. In the current coronavirus disease 2019 pandemic situation and the very rapid development of ICT, learning physics using the Kinemaster and Quizziz applications can be one of the learning media that can be used in the teaching and learning process of physics to improve student learning outcomes by creating a pleasant learning atmosphere. This study uses the Class Action Research (CAR) method for students of class X MIPA II SMA Negeri 2 Langowan. With the number of students 19 people. The results of the evaluation of teaching and learning activities at the stage of the first cycle showed the value of classical X MIPA II students' learning outcomes that was 100%, where there was only 1 student whose learning outcomes were categorized as moderate, 8 students whose learning outcomes were categorized as high and 10 students whose learning outcomes were categorized very high. The results of the research obtained in the learning process using the Kinemaster and Quizziz applications on the material of straight motion can improve the learning outcomes of students of class X MIPA II at SMA Negeri 2 Langowan.